2015
DOI: 10.1523/jneurosci.1717-15.2015
|View full text |Cite
|
Sign up to set email alerts
|

Medial–Frontal Stimulation Enhances Learning in Schizophrenia by Restoring Prediction Error Signaling

Abstract: Posterror learning, associated with medial-frontal cortical recruitment in healthy subjects, is compromised in neuropsychiatric disorders. Here we report novel evidence for the mechanisms underlying learning dysfunctions in schizophrenia. We show that, by noninvasively passing direct current through human medial-frontal cortex, we could enhance the event-related potential related to learning from mistakes (i.e., the error-related negativity), a putative index of prediction error signaling in the brain. Followi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 74 publications
0
39
0
Order By: Relevance
“…Interestingly, though standard treatments do not appear to reduce the magnitude of the ERN, recent studies indicated that manipulating the allocation of attentional resources reduced the ERN in OCD (Klawohn et al, 2016), and that attention bias modification reduced the ERN in healthy adults (Nelson et al, 2015). In addition, there is evidence that transcranial direct-current stimulation (tDCS) can modulate the ERN in patients with schizophrenia (Reinhart et al, 2015). Thus, one intriguing possibility for examination in future research is that supplementing established anxiety treatments with attention training or tDCS may impact the ERN and improve long-term outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, though standard treatments do not appear to reduce the magnitude of the ERN, recent studies indicated that manipulating the allocation of attentional resources reduced the ERN in OCD (Klawohn et al, 2016), and that attention bias modification reduced the ERN in healthy adults (Nelson et al, 2015). In addition, there is evidence that transcranial direct-current stimulation (tDCS) can modulate the ERN in patients with schizophrenia (Reinhart et al, 2015). Thus, one intriguing possibility for examination in future research is that supplementing established anxiety treatments with attention training or tDCS may impact the ERN and improve long-term outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…The learning improvements after inphase stimulation were so dramatic that subjects appeared to immediately reach peak levels of performance, no longer requiring explicit feedback to perform the task at high proficiency ( Fig. 2A, blue lines, blocks [5][6][7][8][9][10][11][12]. This observation was supported by stimulation × feedback interactions for error magnitude [F (1, 29) = 4.527; P = 0.042] and response variability [F (1, 29) = 5.368; P = 0.028] during the poststimulation period.…”
Section: Significancementioning
confidence: 99%
“…Impaired adaptive control is observed in many neurological and neuropsychiatric disorders such as schizophrenia, autism, Alzheimer's disease, attention-deficit/hyperactivity disorder, obsessivecompulsive disorder, Parkinson's disease, and epilepsy (3)(4)(5)(6)(7)(8)(9). Thus, it is not surprising that efforts to improve adaptive control have long characterized the fields of psychology and neuroscience.…”
mentioning
confidence: 99%
“…Fortuitously, frontal midline theta and related ERP features appear to be viable neural mechanisms (Section 3.1), endophenotypes (Kang et al, ; Zlojutro et al, ), diagnostic tools (Figure c), and predictors of treatment response (Burkhouse et al, ; Gorka et al, ) for patient groups defined by frontal dysfunction. These signatures can be up‐ and downregulated with pharmacology (Jocham & Ullsperger, ) and transcranical electric current (Reinhart & Woodman, ; Reinhart, Zhu, Park, & Woodman, ), demonstrating causal control over this signal and downstream effects on network instantiation and behavior in humans.…”
Section: Clinical Practicementioning
confidence: 99%